Association between 2D:4D ratios and sprinting, change of direction ability, aerobic fitness, and cumulative workloads in elite youth soccer players - Nobari, Hadi (2023)
Background The aim of this study was two-fold: (i) to determine the correlation between 2D:4D, maximal oxygen uptake (VO2max), body fat percentage (BF%), maximum heart rate (HRmax), change of direction (COD), and accumulated acute and chronic workload variables; (ii) to verify if the length of the second digit divided by fourth digit (2D:4D) can explain fitness variables and accumulated training load. Methods Twenty elite young football players (age: 13.26±0.19 years; height: 165.8±11.67 cm; body mass: 50.70±7.56 kg; VO2max, 48.22±2.29 ml.kg−1 .min−1 ) participated in the present study. Anthropometric and body composition variables (e.g., height, body mass, sitting height, age, BF%, body mass index, right and left finger 2D:4D ratios) were measured. The following fitness tests were also conducted: 30−15 Intermittent Fitness Test (VO2max and HRmax), COD (5-0-5 agility test), and speed (10-30msprint test. HRmax and the training load were also measured and monitored using the Rate of Perceived Exertion during the 26 weeks. Results There were associations between HRmax and VO2max, between 2D and 4D lengths and Left and Right hand ratios. Also, in AW with Right and Left 4D. The CW and de ACWR with the Right 4D. There were other associations between physical test variables and workload variables. Conclusions Under-14 soccer players with low right and left-hand 2D:4D ratios did not perform better in the selected fitness tests to assess VO2max, COD, or sprint ability. However, it cannot be ruled out that the absence of statistically significant results may be related to the small sample size and the maturational heterogeneity of the participants.